Comparative long-term outcomes of first-line CDK4/6 inhibitors plus endocrine therapy versus endocrine therapy in patients with HR+/HER2-metastatic or advanced breast cancer: a meta-analysis - Wang, Xiaojian; Liang, Xinyi; Li, Chenchen; Qin, Mengtian; Wu, Jianyu; Qin, Yuechen; Zou, Yue; Zeng, Haijian; Li, Chunlan; Huang, Xiaomeng; Tao, Haiyun; Quan, Jieru; et al. (Frontiers in Pharmacology, 2025)
IntroductionThis meta-analysis was designed to compare the long-term outcomes of first-line cyclin-dependent kinase 4/6 (CDK4/6) inhibitors plus endocrine therapy (ET) versus ET in patients with HR+/HER2-metastatic or advanced breast cancer (BC).Materials and methodsFour databases (Medline, Embase, Web of Science, and CENTRAL) were searched for literature comparing First-line CDK4/6 inhibitors plus ET to ET in patients with HR+/HER2-metastatic or advanced breast cancer. The search was conducted from the database’s establishment to April 3, 2025. Progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and severe treatment-related adverse events (SAEs) were subjected to meta-analyses.ResultsTwelve Randomized controlled trials (RCTs) were included in the meta-analysis. The meta-analysis included a group of 4,957 patients diagnosed with HR+/HER2-metastatic or advanced breast cancer. Within this cohort, 2,877 patients were administered First-line CDK4/6 inhibitors together with ET, while 2080 patients received first-line ET alone. Compared with ET, First-line CDK4/6 inhibitors plus ET yielded superior ORR (RR = 1.39, 95% CI, 1.28 to 1.51, P < 0.01), DCR (RR = 1.09, 95% CI, 1.05 to 1.14, P < 0.01), PFS (HR: 0.57, 95%CI 0.53 to 0.62, P < 0.01) and OS (HR: 0.81, 95%CI 0.73 to 0.89, P < 0.01). Reconstruction of Kaplan-Meier curves for OS and PFS using the IPDformKM program provided a clear and comprehensible representation of oncological outcomes. First-line CDK4/6 inhibitors plus ET was more effective than ET in terms of PFS (median survival time: 27.0 months versus 14.4 months, HR: 0.55, 95%CI 0.51 to 0.59, P < 0.01) and OS (median survival time: 59.6 months versus 50.0 months, HR: 0.79, 95%CI 0.72 to 0.87, P < 0.01). With regards to safety, First-line CDK4/6 inhibitors plus ET exhibited a greater likelihood of encountering SAEs (RR = 1.54, 95% CI: 1.30 to 1.82, P < 0.01) in comparison to ET.ConclusionThe present meta-analysis reported comparative long-term outcomes of CDK4/6 inhibitors plus ET versus ET as first-line therapy for HR+/HER2-metastatic or advanced breast cancer. Compared with ET alone, CDK4/6 inhibitors plus ET as first-line therapy provided improved ORR, DCR, PFS, and OS. Furthermore, the heightened efficacy of CDK4/6 inhibitors plus ET was accompanied by a rise in SAEs.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024590572, Identifier CRD42024590572.